Distal Consequences of Mucosal Infections in Intestinal and Lung Inflammation - Melo-González, Felipe; Sepúlveda-Alfaro, Javiera; Schultz, Bárbara M.; Suazo, Isidora D.; Boone, David L.; Kalergis, Alexis M.; Bueno, Susan M. (Frontiers in Immunology, 2022)
Infectious diseases are one of the leading causes of morbidity and mortality worldwide, affecting high-risk populations such as children and the elderly. Pathogens usually activate local immune responses at the site of infection, resulting in both protective and inflammatory responses, which may lead to local changes in the microbiota, metabolites, and the cytokine environment. Although some pathogens can disseminate and cause systemic disease, increasing evidence suggests that local infections can affect tissues not directly invaded. In particular, diseases occurring at distal mucosal barriers such as the lung and the intestine seem to be linked, as shown by epidemiological studies in humans. These studies suggest a strong correlation between inflammatory chronic lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD), and gastrointestinal diseases, such as IBD and irritable bowel disease. However, the effects observed in such distal places are still incompletely understood. Most of the current research focuses on the systemic impact of changes in microbiota and bacterial metabolites during infection, which could further modulate immune responses at distal tissue sites. Here, we review recent murine and human studies linking infectious diseases with changes occurring at distal mucosal barriers, with particular emphasis on bacterial and viral infections affecting the lung and the gastrointestinal tract. Further, we discuss the potential mechanisms by which pathogens may cause such effects, promoting either protection or susceptibility to secondary infection.